The effect of prior androgen synthesis inhibition on outcomes of subsequent therapy with docetaxel in patients with metastatic castrate‐resistant prostate cancer: Results from a retrospective analysis of a randomized phase 3 clinical trial (CALGB 90401) (Alliance). Issue 20 (31st July 2013) - Aggarwal, Rahul; Halabi, Susan; Kelly, William Kevin; George, Daniel; Mahoney, John F.; Millard, Frederick; Stadler, Walter M.; Morris, Michael J.; Kantoff, Philip; Monk, J. Paul; Carducci, Michael; Small, Eric J.; et al.
Abstract : BACKGROUND: Preliminary data suggest a potential decreased benefit of docetaxel in patients with metastatic, castration‐resistant prostate cancer (mCRPC) who previously received abiraterone acetate, a novel androgen synthesis inhibitor (ASI). Cancer and Leukemia Group B (CALGB) trial 90401 (Alliance), a phase 3 trial in patients with mCRPC who received docetaxel‐based chemotherapy, offered the opportunity to evaluate effect of prior ketoconazole, an earlier generation ASI, on clinical outcomes after docetaxel. METHODS: In CALGB trial 90401, 1050 men with chemotherapy‐naive mCRPC were randomized to receive treatment with docetaxel and prednisone that included either bevacizumab or placebo. In total, 1005 men (96%) had data available regarding prior ketoconazole therapy. The observed effects of prior ketoconazole on overall survival (OS), progression‐free survival (PFS), prostate‐specific antigen (PSA) decline, and the objective response rate (ORR) were assessed using proportional hazards and Poisson regression methods adjusted for validated prognostic factors and treatment arm. RESULTS: Baseline characteristics between patients who did (N = 277) and did not (N = 728) receive prior ketoconazole therapy were similar. There were no statistically significant differences between patients who did and those who did not receive prior ketoconazole therapy with respect to OS (median OS, 21.1 months vs 22.3 months, respectively; stratified log‐rank P  = .635), PFS (median PFS, 8.1 months vs 8.6 months, respectively; stratified log‐rank P  = .342), the proportion achieving a decline ≥50% in PSA (61% vs 66%, respectively; relative risk, 1.09; adjusted P  = .129), or ORR (39% vs 43%, respectively; relative risk, 1.11; adjusted P  = .366). CONCLUSIONS: As measured by OS, PFS, PSA, and the ORR, there was no evidence that prior treatment with ketoconazole had an impact on the clinical outcomes of patients with mCRPC who received subsequent docetaxel‐based therapy. The current results highlight the need for prospective studies to assess for potential cross‐resistance with novel ASIs and to define the optimal sequence of therapy in mCRPC. Cancer 2013;119:3636–3643 . © 2013 American Cancer Society . Abstract : A retrospective analysis of patients with metastatic, castrate‐resistant prostate cancer who receive docetaxel‐based chemotherapy on a randomized phase 3 clinical trial (CALGB 90401) does not provide evidence of an adverse impact of prior androgen synthesis inhibition with ketoconazole on subsequent clinical outcomes, contrary to preliminary evidence of cross‐resistance between these modalities of therapy. The study results may have implications for the sequencing of novel androgen synthesis inhibitors and taxane‐based chemotherapy, highlighting the need for prospective, randomized clinical trials to define the optimal sequence of therapy for metastatic, castration‐resistant prostate cancer.